SOSIALISASI APLIKASI PEMINJAMAN DAN PENGEMBALIAN REKAM MEDIS SEBAGAI MEDIA PEMBELAJARAN MAHASISWA/I REKAM MEDIS STIKES DHARMA LANDBOUW PADANG - Fitriani, Yulia; Maisa Putra, Deni; Novita, Dian; Handam Dewi, Siti; Alfauzain (Indonesian Journal of Health Information Management Services, 2024)
Electronic Medical Record Storage is an activity of storing data on digital-based media in health service facilities. Based on the results of interviews with level 2 students, it was found that there is no application for borrowing and returning medical record files for learning on campus. The aim of this research is to design a system. borrowing and returning medical records as a learning medium for students of STIKES Dharma Landbow Padang. This type of research uses the Research and Development development method. This research was carried out at STIKES Dharma Landbouw Padang in December 2022 - July 2023. The population in this research is RMIK level 2 students with a sample size of 50 people taken by Simple Random Sampling. This research was carried out using interviews and observations, the data was processed using computerization. The research results showed that the flow of borrowing and returning medical record files at the STIKES Dharma Landbouw Padang campus had been done manually in expedition books and treacers, but now it has developed with the design of an application for borrowing and returning medical record files which produces output and uses a black box. which means the application is running well according to student needs. Based on the research results, it can be concluded that there is a need for learning, practice and development of the application system for borrowing and returning medical record files by the STIKES Dharma Landbouw Padang campus in order to make it easier and shorten the time for students to store and return medical record files in order to train students before going out into the field for street vendors or work later.